Social Ecology, Climate Resilience and Sustainability in the Tropics: Special Issue - Duguma, L.A.; Minang, Peter A. (2021)
This Special Issue addresses the wide knowledge gap in how social ecology could influence both the resilience agenda and sustainability at local and global scales. It covers the missing link on how people at multiple scales could play a crucial role in addressing climate change from multiple angles through nurturing ecosystems.